THE ARBITRARY NATURE OF SIGNS AND REDUCED FORMS SEEN IN THE LONE RANGER MOVIE - Buyun Khulel (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2020)
This present study provided analysis on the arbitrary nature of signs and reduced forms (gonna, wanna, and gotta) seen in the Lone Ranger movie. The researcher focused on the dialogues between the main characters of the movie (John Reid abbreviated as “JR” and Tonto abbreviated as “T”). The researcher found in the script of the movie that Tonto used some terms related to the arbitrary nature of signs. Those terms are Spirit Walker, Windigo, and Kemosabe. Those terms have no logical basis for the choice of a particular signal to refer to a particular signification. This study also analyzed some reduced forms used by the main characters in the Lone Ranger movie. Reduced forms frequently used in speech in informal colloquial English, particularly American English. This study revealed only one kind of reduced forms found in the dialogue between the main characters. That kind of reduced form is “gonna”. The researcher found that “gonna” was spoken three times in the movie. All of them were spoken by John Reid (JR). in line with the previous research, those findings showed that “gonna” usually spoken by young people and comes from certain social class.